2022
DOI: 10.1371/journal.pmed.1004033
|View full text |Cite
|
Sign up to set email alerts
|

Performance bonuses and the quality of primary health care delivered by family health teams in Brazil: A difference-in-differences analysis

Abstract: Background Pay-for-performance (P4P) programmes to incentivise health providers to improve quality of care have been widely implemented globally. Despite intuitive appeal, evidence on the effectiveness of P4P is mixed, potentially due to differences in how schemes are designed. We exploited municipality variation in the design features of Brazil’s National Programme for Improving Primary Care Access and Quality (PMAQ) to examine whether performance bonuses given to family health team workers were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…One study found a positive association between bonus payments to FHTs based on overall performance in primary health care compared to no bonus. Additionally, the magnitude of the associations increased with the amount paid to FHTs, suggesting a doseresponse relationship (Fardousi et al, 2022). Although the present study identified improved work process performance in FHTs that received PMAQ resources, this was not associated with better results when compared to those that did not.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…One study found a positive association between bonus payments to FHTs based on overall performance in primary health care compared to no bonus. Additionally, the magnitude of the associations increased with the amount paid to FHTs, suggesting a doseresponse relationship (Fardousi et al, 2022). Although the present study identified improved work process performance in FHTs that received PMAQ resources, this was not associated with better results when compared to those that did not.…”
Section: Discussioncontrasting
confidence: 65%
“…Although the present study identified improved work process performance in FHTs that received PMAQ resources, this was not associated with better results when compared to those that did not. Our findings were based on comparisons between Cycles 2 and 3, whereas the aforementioned study (Fardousi et al, 2022) analyzed Cycles 1 and 3, which could partially explain the different results. Moreover, our focus was on work processes, whereas the other authors investigated overall performance, including process, structure and outcome indicators.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The relatively small size of payments in HIC as compared to LMICs is worthy of note. Recent research highlights that schemes paying a higher bonus increase performance more (Fardousi et al. , 2022) Schemes in HIC may therefore see improvements with larger bonuses.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small size of payments in HIC as compared to LMICs is worthy of note. Recent research highlights that schemes paying a higher bonus increase performance more (Fardousi et al, 2022) Schemes in HIC may therefore see improvements with larger bonuses. Conversely, the same research found that providers in poorer areas increased performance even in response to relatively small incentives, suggesting that also smaller incentive sizes could lead to performance improvements in LMIC (ibid), which may increase the efficiency and financial sustainability of these schemes.…”
Section: Design Characteristicsmentioning
confidence: 99%